Risk Factors for Premature Hair Graying in Young Turkish Adults. Issue 4 (13th June 2016) - Akin Belli, Asli; Etgu, Fatma; Ozbas Gok, Seyran; Kara, Bilge; Dogan, Gursoy
Abstract: Background: Premature hair graying (PHG) is a common condition resulting in loss of self‐esteem. Studies investigating PHG risk factors for both sexes with a large number of patients are scarce. We sought to investigate the socioclinical risk factors for PHG in young Turkish men and women and the differences between the sexes. Methods: A cross‐sectional study was conducted in 1, 119 participants who answered a survey about PHG and some socioclinical characteristics between February and July 2015. The number of gray hairs, onset age of hair graying, and family history of PHG were asked about, as well as demographic characteristics, anthropometric measures, body mass index, smoking, alcohol consumption, sports life, diet, medical history, educational status, occupation, marital status, monthly income, and Fitzpatrick skin type. Results: Of 1, 119 participants, 315 (28.1%) had PHG and 804 did not. Maternal and paternal PHG, alcohol consumption, presence of chronic disease, educational status, hair loss, perceived stress scale (PSS) score, age, and height were significantly higher in subjects with PHG. Rates of maternal and paternal PHG were high in women with PHG, and the rate of paternal PHG was high in men with PHG. According to the multivariate ordinal regression analysis, PSS score, age, hair loss, and family history of PHG were correlated with the severity of PHG. Conclusion: PHG is closely related to factors causing oxidative stress, such as emotional stress, alcohol consumption, and chronic diseases in genetically predisposed men and women.